Bacteria-triggered release of a potent biocide from core-shell polyhydroxyalkanoate (PHA)-based nanofibers for wound dressing applications. Issue 3 (11th February 2020) - Li, Wei; Cicek, Nazim; Levin, David B.; Logsetty, Sarvesh; Liu, Song
Abstract: Bacterial infections are a serious issue in wound healing. Extensive use of biocides in wound dressings have raised concerns of biocide resistance and unnecessary harm to normal skin cells. In this paper, we report a new approach to realize bacteria-triggered release of a biocide to the sites of bacterial infections from core-shell polyhydroxyalkanoate (PHA)-based nanofibers prepared by coaxial electrospinning. The hydrophobic PHA-based shell can prevent the biocide from undesirable payload release in physiological environments without pathogens. However, in the presence of pathogens, the PHA-based shell is degraded by the pathogens, and the encapsulated biocide is released. The released biocide subsequently can exert targeted antimicrobial effects on the bacteria. Using Pseudomonas aeruginosa as a model bacterium and dodecyltrimethylammonium chloride as a model biocide, we demonstrated that the core-shell PHA-based nanofibers effectively released encapsulated dodecyltrimethylammonium chloride in the presence of Pseudomonas aeruginosa, resulting in targeted inactivation of Pseudomonas aeruginosa cells. Highlights: Unique core-shell nanofibers were successfully fabricated from PHAs generated by bacteria. An on-demand release of biocide was achieved from a PHA-based core-shell nanofibours membrane. The membrane's mechanical properties closely match those of the human skin.